Blonanserin extensively occupies rat dopamine D3 receptors at antipsychotic dose range - Satoko Baba; Takeshi Enomoto; Tomoko Horisawa; Takashi Hashimoto; Michiko Ono (Elsevier, 2015)
Antagonism of the dopamine D3 receptor has been hypothesized to be beneficial for schizophrenia cognitive deficits, negative symptoms and extrapyramidal symptoms. However, recent animal and human studies have shown that most antipsychotics do not occupy D3 receptors in vivo, despite their considerable binding affinity for this receptor in vitro. In the present study, we investigated the D3 receptor binding of blonanserin, a dopamine D2/D3 and serotonin 5-HT2A receptors antagonist, in vitro and in vivo. Blonanserin showed the most potent binding affinity for human D3 receptors among the tested atypical antipsychotics (risperidone, olanzapine and aripiprazole). Our GTPγS-binding assay demonstrated that blonanserin acts as a potent full antagonist for human D3 receptors. All test-drugs exhibited antipsychotic-like efficacy in methamphetamine-induced hyperactivity in rats. Treatment with blonanserin at its effective dose blocked the binding of [3H]-(+)-PHNO, a D2/D3 receptor radiotracer, both in the D2 receptor-rich region (striatum) and the D3 receptor-rich region (cerebellum lobes 9 and 10). On the other hand, the occupancies of other test-drugs for D3 receptors were relatively low. In conclusion, we have shown that blonanserin, but not other tested antipsychotics, extensively occupies D3 receptors in vivo in rats.